Vitamin D level in COVID-19 patients has positive correlations with autophagy and negative correlations with disease severity - Dong, Hongna; Hao, Yuqiu; Gao, Peng (Frontiers in Pharmacology, 2024)
Background and Objectives: There is still incomplete understanding of the pathogenesis of COVID-19. Calcitriol, the main form of vitamin D in serum, regulates immune responses and increases resistance to pathogens, but the mechanism by which it protects against COVID-19 is uncertain. Autophagy has antiviral effects and helps to maintain homeostasis, but its specific role in COVID-19 is also uncertain. Both vitamin D and autophagy have important functions in the lung microenvironment. This study examined the relationship of serum vitamin D and autophagy-related proteins in patients with COVID-19 and evaluated their potential use as biomarkers. Methods: Blood samples from COVID-19 patients at the Second Hospital of Jilin University were collected. The levels of vitamin D, autophagy-related proteins (Becline 1 [BECN1] and autophagy-related 7 [ATG7]), and inflammatory markers (TNF-α and IL-1β) were measured using enzyme-linked immunosorbent assays. Results: We examined 25 patients with mild/moderate COVID-19 and 27 patients with severe/critical COVID-19. The group with severe/critical COVID-19 had more abnormalities in many laboratory indicators, including lower levels of autophagy markers (BECN1 and ATG7) and vitamin D, and higher levels of inflammatory markers (TNF-α and IL-1β). Partial correlation analysis showed that vitamin D had strong positive correlations with ATG7 (r = 0.819, P < 0.001) and BECN1 (r = 0.900, P < 0.001). Conclusion: Our results demonstrated that the vitamin D level had significant negative correlations with COVID-19 severity and strong positive correlations with autophagy. These findings enhance our understanding of the pathogenesis of COVID-19, and provide a theoretical basis for clinical interventions that target autophagy and vitamin D.